Alternative Intrabladder Manometry Technique for the Indirect Measurement of Intra-abdominal Pressure in Horses - Canola, Paulo Alescio [UNESP]; Perotta, Joao Henrique [UNESP]; Martins Dias, Deborah Penteado [UNESP]; Canola, Julio Carlos [UNESP]; Johnson, Philip J.; Araujo Valadao, Carlos Augusto [UNESP] (Elsevier B.V., 2012)
Although indirect methods for estimating intra-abdominal pressure (IAP) have been extensively studied in humans, mainly for identification of IAP increments in critical care unit patients (life-threatening condition), little work has been performed in veterinary medicine, especially in horses. The standard method of acquisition of intrabladder pressure (IBP) in human subjects (fluid-filled system with no balloon distention) has been previously evaluated in horses with an unfavorable outcome. Therefore, we re-examined the previously performed method of IBP investigation in horses by using an air-filled intrabladder manometry system in female horses. Intrabladder pressure was estimated by air-filled balloon manometry in seven healthy adult mares. The results were compared with two sets of directly acquired IAP values obtained by right paralumbar puncture using an 8-G needle in seven horses. Direct IAP values were obtained at times unrelated to IBP measurement acquisitions, and three of the seven horses used (for direct IAP measurement) were different animals from the mares used for assessment of IBP. Both sets of IAP measurements yielded subatmospheric values (IAP(1) = 10.5 +/- 2.2 mm Hg; IAP(2) = 11.6 +/- 2.0 mm Hg). Slightly subatmospheric IBP values were also recorded in some mares, but the mean ( SD) IBP was 1.4 +/- 2.0 mm Hg. There was no correlation between IBP and IAP. These results suggest that this indirect (IBP) method for estimating IAP is not applicable for female horses. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Equine; Intra-abdominal hypertension; Abdominal Compartment syndrome; Intrabladder catheter; Intravesical pressure